2017
DOI: 10.5539/jfr.v6n4p44
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Lactic Acid Bacteria for the Optimized Production of Sheep’s Milk Yogurt with a High Conjugated Linoleic Acid Content

Abstract: Thirty-five different lactic acid bacteria (LAB) strains were screened for their conjugated linoleic acid (CLA) isomers (C18:2 cis-9, trans-11 and C18:2 trans-10, cis-12) producing ability from linoleic acid (LA) in sheep's milk. Preliminary experiments revealed that Lactobacillus delbrüeckii ssp. bulgaricus 2230 and Streptococcus thermophilus St 360 among the screened strains had the highest CLA-producing ability. This two strains were assayed in an 11-run fractional factorial design to investigate the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…bulgaricus LBP UFSC 2230 exceeded that of S. thermophilus strain 360, the LBP UFSC 2230 culture demonstrated the potential ability to synthesize the c 9, t 11-C 18:2 isomer, but the production of the t 10, c 12-C 18:2 was not observed. Nevertheless, in the opposite condition, there was a significant detection of the latter isomer ( 3 ).…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…bulgaricus LBP UFSC 2230 exceeded that of S. thermophilus strain 360, the LBP UFSC 2230 culture demonstrated the potential ability to synthesize the c 9, t 11-C 18:2 isomer, but the production of the t 10, c 12-C 18:2 was not observed. Nevertheless, in the opposite condition, there was a significant detection of the latter isomer ( 3 ).…”
Section: Discussionmentioning
confidence: 89%
“…It has previously been reported that L. delbrueckii subsp. bulgaricus LBP UFSC 2230 was the most efficient CLA producer among 13 strains of the same species ( 3 ). In the current study, we assessed the ability of OleH from L. delbrueckii subsp.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations